Health interventions and its impact on outcomes among diabetic patients: A systematic review - Krisnadewi, Kadek Ida; Kristina, Susi Ari; Endarti, Dwi; Andayani, Tri Murti (Mahidol University - Faculty of Pharmacy, 2022)
Studies related to the prevention of diabetes mellitus have developed rapidly, from effectiveness research to implementation research. However, effective implementation of diabetes programs and evidence of their impact on the population should be produced by means other than measuring the effectiveness of the program. We reviewed the results of systematic reviews focused on diabetes prevention programs and the outcomes of those programs in a real-world setting. A systematic review of the program aimed at assessing or measuring the outcome of preventive programs in individual prediabetes, moderate or high-risk diabetes. In September 2021, an article search was performed on PubMed, Science Direct, and SAGE Journal databases. We have reviewed all the articles published in the last ten years. The exclusion criteria were studies published before 2011. The number of diabetic participants is unknown and the method is incomplete. Eight studies were included in the review. All information about participation and programs. Most of all studies were cohort and RCT studies. All interventions showed positive changes (efficacy) based on weight loss, HbA1C, blood glucose levels, and BMI. Rapid studies have shown that the risk of diabetes is reduced. Our results show that the strength of the program plays an important role in the outcome of weight loss. Programs with different variations (education, Community Health worker, diet, physical activity) have had a positive effect on reducing the risk of diabetes in the population.